Framing of controversial caricatures of Prophet Muhammad: a study of two Malaysian Mainstream Newspapers - Dafrizal; Faridah Ibrahim; Fauziah Ahmad (Universiti Kebangsaan Malaysia, 2011)
In early 2006, the world was once again shaken by a global controversy. This time it was the act of a Danish newspaper, Jyllands-Posten which had boldly published twelve controversial caricatures of Prophet Muhammad. There was a big outcry worldwide especially from the Muslim countries protesting on this act. Issues and debates were raised in the mass media and by many Muslim countries and their leaders, and without exception,Malaysia had joined in this worldwide protest. However,Malaysia had gone a step further in reprimanding the media which had joined in the league to publish the caricatures. Several newspapers were ordered to stop publishing and the editors were summoned to defend their actions. This study aims to see how the Malaysian mainstream media frame the controversial issue of the caricature of Prophet Muhammad.